Molecular Analysis of Tetracycline Resistance in Pasteurella aerogenes - Kehrenberg, Corinna (American Society for Microbiology, 2001)
Tetracycline-resistant Pasteurella aerogenes isolates obtained from the intestinal tract of swine were investigated for their tet genes by PCR analysis and hybridization experiments. In contrast to Pasteurella isolates from the respiratory tract, tet(H) genes were detected in the chromosomal DNA of only 2 of the 24 isolates, one of which also carried two copies of a tet(B) gene. All other P. aerogenes isolates carried tet(B) genes, which are the predominant tet genes among Enterobacteriaceae. A single isolate harbored a tet(B) gene as part of a truncated Tn10 element on the 4.8-kb plasmid pPAT2. Comparative analysis of the pPAT2 sequence suggested that the Tn10 relic on plasmid pPAT2 is the result of several illegitimate recombination events. The remaining 21 P. aerogenes isolates carried one or two copies of the tet(B) gene in their chromosomal DNA. In the majority of the cases, these tet(B) genes were associated with copies of Tn10 as confirmed by their SfuI and BamHI hybridization patterns. No correlation between the number of tet gene copies and the MICs of tetracycline, doxycyline and minocycline was observed.